2014
DOI: 10.14336/ad.2013.0400235
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Clinical and Cognitive Variables with Brain Morphometric Abnormalities in Alzheimer’s Disease: a Voxel Based Morphometric Study Using 3-Tesla MRI

Abstract: Alzheimer's disease (AD) is associated with widespread structural and functional brain alterations. The current study examined the gray matter (GM) voxel based morphometric (VBM) correlates of cognitive and clinical severity scores in patients with AD. The study included 34 patients with AD according to NINCDS/ADRDA AD criteria and 28 matched elderly controls. All subjects were clinically evaluated using Hindi Mental Status Examination (HMSE), Everyday Abilities Scale for India (EASI) and the Clinical Dementia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Briefly, VBM assesses whole-brain structures with voxel-by-voxel comparisons that can be used to compare tissue concentrations or volumes between subject groups to distinguish structural alterations [ 12 ]. The VBM technique has been widely used to assess the gray matter (GM) and white matter (WM) alterations in various brain diseases such as Alzheimer's disease [ 13 - 15 ], Parkinson's disease [ 16 ], and epilepsy [ 17 ]. We used the VBM technique in the present study to determine the overall and regional brain volume differences among healthy male and female young (~late 20s) and older (~late 60s) individuals.…”
mentioning
confidence: 99%
“…Briefly, VBM assesses whole-brain structures with voxel-by-voxel comparisons that can be used to compare tissue concentrations or volumes between subject groups to distinguish structural alterations [ 12 ]. The VBM technique has been widely used to assess the gray matter (GM) and white matter (WM) alterations in various brain diseases such as Alzheimer's disease [ 13 - 15 ], Parkinson's disease [ 16 ], and epilepsy [ 17 ]. We used the VBM technique in the present study to determine the overall and regional brain volume differences among healthy male and female young (~late 20s) and older (~late 60s) individuals.…”
mentioning
confidence: 99%
“…A number of neuroimaging studies have reported structural brain abnormalities in patients with AD (Bagepally et al, 2013;Clerx et al, 2013;Jack et al, 2008;Tang et al, 2014;van de Pol et al, 2006). Atrophy of the hippocampus on MRI is considered a valid biomarker of AD neuropathology, even though the measurement of hippocampal volume is not used in routine clinical care in the diagnosis of AD.…”
Section: Introductionmentioning
confidence: 99%